PERAN "MIGRANT CARE" DALAM PERLINDUNGAN PEKERJA MIGRAN PEREMPUAN INDONESIA DI MALAYSIA PERIODE 2018-2020 - Retha Syalva Ardhyageraneta, (2022)
This research argued about the role of Migrant CARE is very significant to support the rule of government to assist, monitor, and protect Indonesian female migrant workers in Malaysia using the International Organization theory proposed by Clive Archer. Where there are three roles of the International Organization itself an instrument, an arena, and also as an independent. The author uses descriptive qualitative research methods that use primary and secondary data sources. The data collection technique that the author uses is by conducting interviews and literature studies. The author uses qualitative data analysis techniques in conducting data analysis which will later be associated with theories and concepts as analytical references. In this study, Migrant CARE seeks to assist the Indonesian government in reducing the number of cases of violence against Indonesian female migrant workers in Malaysia through programs available at Migrant CARE, namely consultation, advocacy, research, education, and Migrant CARE's actions in urging the two countries. both Indonesia and Malaysia to take part in handling cases of violence against Indonesian migrant workers in Malaysia. Keywords: Migrant CARE, International Organizations, Indonesian Women Migrant Workers in Malaysia, Violent Discrimination.